Christian Leadership in the Church, Education, and the Public Sphere: Reviewed from the Urgency of Character Renewal - Sidjabat, Binsen Samuel (Didache: Journal of Christian Education, 2025)
This paper discusses the urgency of renewing the character of Christian leaders in churches, schools, and public spaces. This research was conducted through a literature review to explore the challenges faced by leaders as they age. It researched the importance of improving the character of educators as leaders, and explored the understanding of Tom Yeakley, N.T. Wright, Marvin Oxenham, and Andar Ismail on character formation. Based on a review of the literature, it is stated that Christian leaders bring the impact of their past personal formation into their duties and roles in ministry. It was also stated that the renewal of the character of Christian leaders in Indonesia is very necessary and that it has a theological, theoretical, and practical basis. The thoughts in this paper are expected to be beneficial for the church and Christian education.